2018
DOI: 10.1021/jacs.7b12865
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Controlled Chemoselective C(acyl)–O Bond vs C(aryl)–C Bond Activation of Aromatic Esters in Nickel Catalyzed C(sp2)–C(sp3) Cross-Couplings

Abstract: A ligand-controlled and site-selective nickel catalyzed Suzuki-Miyaura cross-coupling reaction with aromatic esters and alkyl organoboron reagents as coupling partners was developed. This methodology provides a facile route for C(sp)-C(sp) bond formation in a straightforward fashion by successful suppression of the undesired β-hydride elimination process. By simply switching the phosphorus ligand, the ester substrates are converted into the alkylated arenes and ketone products, respectively. The utility of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(78 citation statements)
references
References 118 publications
2
74
0
1
Order By: Relevance
“…The introduction of alkyl groups by transition metal catalysis has always been very difficult due to the competing β‐hydride elimination. As a part of research interest aimed at promoting alkylation protocols via C−O bond activation and functionalization, Rueping group demonstrated the possibility to achieve a Suzuki–Miyaura type decarbonylative alkylation reaction of carboxylic acid esters . With 10 mol % Ni(cod) 2 as catalyst and 20 mol % dcype as the supporting ligand, a wide variety of aromatic and heteroaromatic esters were coupled with structurally diverse B ‐alkyl‐9‐BBNs possessing β‐hydrogens in good to moderate yields (Scheme ).…”
Section: Carbon–carbon Bond Forming Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of alkyl groups by transition metal catalysis has always been very difficult due to the competing β‐hydride elimination. As a part of research interest aimed at promoting alkylation protocols via C−O bond activation and functionalization, Rueping group demonstrated the possibility to achieve a Suzuki–Miyaura type decarbonylative alkylation reaction of carboxylic acid esters . With 10 mol % Ni(cod) 2 as catalyst and 20 mol % dcype as the supporting ligand, a wide variety of aromatic and heteroaromatic esters were coupled with structurally diverse B ‐alkyl‐9‐BBNs possessing β‐hydrogens in good to moderate yields (Scheme ).…”
Section: Carbon–carbon Bond Forming Reactionsmentioning
confidence: 99%
“…As ap art of research interesta imed at promoting alkylation protocols via CÀOb ond activation and functionalization, [13] Rueping group demonstrated the possibility to achieve aS uzuki-Miyaura type decarbonylative alkylation reaction of carboxylic acid esters. [14] With 10 mol %N i(cod) 2 as catalysta nd 20 mol %dcype as the supporting ligand,awide variety of aromatic and heteroaromatic esters were coupled with structurally diverse B-alkyl-9-BBNs possessing b-hydrogens in good to moderate yields (Scheme 10). The utility of this protocolh as been demonstrated by the broad functional group tolerance and application to the synthesis of bioactive compounds.A t the same time, the authors also demonstrated that switching the ligand from dcype to PnBu 3 or PCy 3 favors the ketone formation rather than decarbonylative coupling.…”
Section: Suzuki-miyaura-type Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Despite the usefulness of this transformation,t wo major issues emerge especially at larger scale:a )Contamination of potentially bioactive products with metals and b) the recovery of Pd metal. [12] Thus, there is much potential to develop more efficient Nibased version of the Fukuyama coupling. of the organozinc reagent was required in combination with long reactiont imes (20 h).…”
mentioning
confidence: 99%
“…Recently,k etonesw ere accessed by Rueping et al from the more inert aromatic oxoesters anda lkylboranes under Ni(cod) 2 catalysis. [12] Thus, there is much potential to develop more efficient Nibased version of the Fukuyama coupling. We were interested if the salt effect of Knochel-type arylzinc reagents could be employedt oi ncreaser eactivity in the Ni-catalyzed Fukuyama reaction allowing for reduced catalystl oadings and shorter reaction times.…”
mentioning
confidence: 99%